Disorientasi Tafsir Bahasa Abdul Wahab Fayd: Kajian atas Ad-Dakhil fi Tafsir Al-Qur’an Al-Karim - Abdul Hanan (IIQ An Nur Yogyakarta, 2025)
This article reviews Ad-Dakhil fi Tafsir al-Qur’an al-Karim, a book by Abdul Wahab Fayd that discusses the discourse on deviations in the interpretation of the Qur’an. The focus of this review lies in three key aspects found in volume two, chapter two of the book. First, the aspect of linguistic meaning; second, the rules of Arabic grammar (nahwu); and third, the aspect of Qur’anic recitation (qira’ah). These three aspects serve as a foundation, indicating that Qur’anic interpretation based on linguistics heavily relies on an understanding of these limitations. The book highlights the significant impact of neglecting these elements, particularly the growing superficiality in linguistic interpretation today. This study seeks to answer several questions: what limitations lead to disorientation in linguistic interpretation, what forms of deviation exist, and what constitutes a proper linguistic interpretation. The approach employed is historical, using content analysis as the analytical framework.